Oxidative and osmotolerant effects in Salvator merianae (Squamata: Teiidae) red blood cells during hibernation - Vicente-ferreira, G. S. [UNESP]; Martins, G. S. [UNESP]; Chaves, N. A. [UNESP]; Silva, D. G. H. [UNESP]; Bonini-domingos, C. R. [UNESP] (Instituto Internacional de Ecologia, 2021)
Hibernation is a natural condition of animals that lives in the temperate zone, although some tropical lizards also experience hibernation annually, such as the lizard native from South America, Salvator merianae, or “tegu” lizard. Even though physiological and metabolic characteristic associated with hibernation have been extensively studied, possible alterations in the red blood cells (RBC) integrity during this period remains unclear. Dehydration and fasting are natural consequences of hibernating for several months and it could be related to some cellular modifications. In this study, we investigated if the osmotic tolerance of RBCs of tegu lizard under hibernation is different from the cells obtained from animals while normal activity. Additionally, we indirectly investigated if the RBCs membrane of hibernating tegus could be associated with oxidation by quantifying oxidized biomolecules and the activity of antioxidant enzymes. Our findings suggest that RBCs are more fragile during the hibernation period, although we did not find evidence of an oxidative stress scenario associated with the accentuated fragility. Even though we did not exclude the possibility of oxidative damage during hibernation, we suggested that an increased RBCs volume as a consequence of hypoosmotic blood during hibernation could also affect RBCs integrity as noted.

A hibernação é uma condição natural dos animais que vivem na zona temperada, embora alguns lagartos tropicais também experenciem hibernação anualmente, como é o caso do lagarto nativo da América do Sul, Salvator merianae ou “teiú”. Embora as características fisiológicas e metabólicas associadas à hibernação tenham sido amplamente estudadas, possíveis alterações na integridade das hemácias durante esse período ainda permanecem obscuras. A desidratação e o jejum são consequências naturais da hibernação por vários meses e podem estar relacionadas a algumas modificações celulares. Neste estudo, investigamos se a tolerância osmótica de hemácias do lagarto teiú sob hibernação são diferentes das células obtidas de animais em atividade normal. Além disso, investigamos indiretamente por meio da quantificação de biomoléculas oxidadas e da atividade de enzimas antioxidantes se a membrana das hemácias dos teiús em hibernação poderia estar associada à oxidação. Nossos resultados sugerem que as hemácias possuem maior fragilidade durante o período de hibernação, embora não tenhamos encontrado evidências de um cenário de estresse oxidativo associado à essa fragilidade acentuada. Embora não tenhamos excluído a possibilidade de dano oxidativo durante a hibernação, sugerimos que um aumento no volume das hemácias como consequência de sangue hipoosmótico durante a hibernação também poderia afetar a integridade de hemácias, tal como foi observado.
Efeitos de oxidação e osmotolerância dos eritrócitos de Salvator merianae (Squamata: Teiidae) durante a hibernação
Keywords: tegu; osmotic fragility; erythrocytes; oxidative stress; tegu; fragilidade osmótica; eritrócitos; estresse oxidativo